Influence of Bias Potential Magnitude on Structural Engineering of ZrN-Based Vacuum-Arc Coatings - Sobol, O. V.; Postelnyk, H. O.; Pinchuk, N. V.; Meylekhov, A. A.; Zhadko, M. A.; Andreev, A. A.; Stolbovoy, V. A. (Vasyl Stefanyk Precarpathian National University, 2021)
The creation of the scientific foundations for the structural engineering of ultrathin nanolayers in multilayer nanocomposites is the basis of modern technologies for the formation of materials with unique functional properties. It is shown that an increase in the negative bias potential (from -70 to -220 V) during the formation of vacuum-arc nanocomposites based on ZrN makes it possible not only to control the preferred orientation of crystallites and substructural characteristics, but also changes the conditions for conjugation of crystal lattices in ultrafine (about 8 nm) nanolayers.

Створення наукових основ структурної інженерії надтонких наношарів в багатошарових нанокомпозитах є основою сучасних технологій формування матеріалів з унікальними функціональними властивостями. Показано, що збільшення від’ємного потенціалу зсуву (від -70 до -220 В), при формуванні вакуумно-дугових нанокомпозитів на основі ZrN, дозволяє не тільки управляти переважною орієнтацією кристалітів і субструктурними характеристиками, але і змінює умови сполучення кристалічних решіток в надтонких (близько 8 нм) наношарах.
Вплив величини потенціалу зсуву на структурну інженерію вакуумно-дугових покриттів на основі ZrN
Keywords: vacuum arc; zirconium nitride; multilayer nanocomposites; X-ray structural analysis; nanostructure; interlayer conjugation; texture; substructure; вакуумна дуга; нітрид цирконію; багатошарові нанокомпозити; рентгеноструктурний аналіз; міжшарове сполучення; наноструктура